Automorphism group of certain power graphs of finite groups - Ali Reza Ashrafi; Ahmad Gholami; Zeinab Mehranian (Electronic Journal of Graph Theory and Applications (EJGTA), 2017)
The power graph $\mathcal{P}(G)$ of a group $G$ is the graphwith group elements as vertex set and two elements areadjacent if one is a power of the other. The aim of this paper is to compute the automorphism group of the power graph of several well-known and important classes of finite groups.